2016
DOI: 10.1186/s40478-016-0372-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive protein tyrosine phosphatase mRNA profiling identifies new regulators in the progression of glioma

Abstract: The infiltrative behavior of diffuse gliomas severely reduces therapeutic potential of surgical resection and radiotherapy, and urges for the identification of new drug-targets affecting glioma growth and migration. To address the potential role of protein tyrosine phosphatases (PTPs), we performed mRNA expression profiling for 91 of the 109 known human PTP genes on a series of clinical diffuse glioma samples of different grades and compared our findings with in silico knowledge from REMBRANDT and TCGA databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Some years back, we reviewed a list of PTP genes that bear links to gliomagenesis [ 121 ]. More recently, we classified a subset of PTPs as possible entry points for glioma treatment based on a comparison of their relative expression levels in normal and tumor brain material combined with expression and survival data from relevant databases [ 122 ]. Three of these genes ( PTPRZ1 , PTEN , PTPRT ) encode PTPs with C-terminal PDZ binding motifs [ 116 , 123 ] and mapping of the interacting PDZ domain-containing proteins may be of relevance for glioblastoma etiology.…”
Section: Untying Gordian Knots In Glioblastomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Some years back, we reviewed a list of PTP genes that bear links to gliomagenesis [ 121 ]. More recently, we classified a subset of PTPs as possible entry points for glioma treatment based on a comparison of their relative expression levels in normal and tumor brain material combined with expression and survival data from relevant databases [ 122 ]. Three of these genes ( PTPRZ1 , PTEN , PTPRT ) encode PTPs with C-terminal PDZ binding motifs [ 116 , 123 ] and mapping of the interacting PDZ domain-containing proteins may be of relevance for glioblastoma etiology.…”
Section: Untying Gordian Knots In Glioblastomasmentioning
confidence: 99%
“…This may well involve PTPN13. In addition, for the PDZ target sequence (“SSF”; [ 116 ]) in the glioblastoma-relevant PTPRT [ 122 ] knowledge on the glioblastoma PDZ interactome could provide new therapeutic avenues.…”
Section: Untying Gordian Knots In Glioblastomasmentioning
confidence: 99%
“…Intriguingly, among all the Chinese breeds in our study, the JQ breed had the highest number of SNPs in a block, with 80 SNPs in Block 22 of Chromosome 18 (923784 bp – 1002867 bp). This block overlaps the protein tyrosine phosphatase receptor ( PTPRN2 ) gene, which suggests that it is associated with oncogenic processes ( Bourgonje et al, 2016 ). This gene is also predominantly expressed in endocrine and neuronal cells, where it functions in exocytosis ( Sorokin et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, some of these PRKCG-like genes have already been reported to be closely related with glioma [88][89][90][91][92]. For instance, AKAP6 (A-kinase anchoring protein 6) polymorphisms are associated with glioma susceptibility and prognosis [91]; Phosphorylated SATB1 (SATB homeobox 1) contributes to the invasive and proliferative of GBM cells and is associated with glioma prognosis [88]; Higher expression of CDK17 (cyclin dependent kinase 17) is indicative of longer overall survival [89]; PTPRM (protein tyrosine phosphatase receptor type M) expression is significantly reduced in GBM by contrast to LGG and higher expression is indicative of longer overall survival [90]; and CHD5 (chromodomain helicase DNA binding protein 5) might act as a tumor suppressor and its lower expression is associated with poor prognosis in glioma [92]. Among these PRKCG-like genes, we revealed that 114 genes show negative correlations between methylation level and expression level, whereas 297 genes present positive correlations (Additional file 1: Table S3).…”
Section: Prkcg-like Genes May Present Heterogeneous Roles In Glioma Tmentioning
confidence: 99%